سلوكيات القــيادة التحـويـلية لــدى القـادة الإداريين بالمديـريـة الجهـويـة الصناعية بسكيكدة (DRIK) - دراســة تحــليلية - (El-Wahat Journal for Research and Studies, 2020)
This study aims to identify the level of Transformational leadership behaviours at the administrative leaders in the Regional Industrial Directorate in Skikda (DRIk)For this purpose, the researchers adopted the descriptive analytical approach using the comprehensive survey method for all  enterprise tires A questionnaire was developed as a research tool and distributed to a sample of 92 permanent tires. (directors, and department heads) In DRIk.After data collection and analysis by the statistical program SPSS (v20), the study concluded that the degree of availability of transformational leadership behaviors in different dimensions (Idealized influence, inspirational motivation, individual consideration, intellectual stimulation) was high at the 0.05 level. Key words: leadership,Transformational leadership, Transformational leadership behaviours,  Regional Industrial Directorate in Skikda (DRIk).